Data mining tools for malware detection - Masud, Mehedy; Khan, Latifur; Thuraisingham, Bhavani M. (Auerbach Publications, 2016)
Although the use of data mining for security and malware detection is quickly on the rise, most books on the subject provide high-level theoretical discussions to the near exclusion of the practical aspects. Breaking the mold, Data Mining Tools for Malware Detection provides a step-by-step breakdown of how to develop data mining tools for malware d.